The Relationship between Selenium and T3 in Selenium Supplemented and Nonsupplemented Ewes and Their Lambs - Abd Elghany Hefnawy; Seham Youssef; P. Villalobos Aguilera; C. Valverde Rodríguez; J. L. Tórtora Pérez (Veterinary Medicine International)
Twenty pregnant ewes were selected and classified into two groups. The first group received subcutaneous selenium supplementation (0.1 mg of sodium selenite/kg BW) at the 8th and 5th weeks before birth and 1st week after birth while the other was control group without selenium injection. Maternal plasma and serum samples were collected weekly from the 8th week before birth until the 8th week after birth and milk samples were taken from ewes weekly, while plasma and serum samples were collected at 48 hours, 1st, 2nd, 3rd, 5th, and 8th weeks after birth from the newborn lambs. Results demonstrated significant positive relationship between maternal plasma selenium and serum T3 in supplemented and control ewes (r=0.69 to 0.72, P<0.05). There was significant (P<0.001) increase in T3 in supplemented ewes and their lambs until the 8th week after birth. There was positive relationship between milk, selenium concentration, and serum T3 in the newborn lambs of the supplemented group (r=0.84, P<0.01), while the relationship was negative in the control one (r=-0.89, P<0.01). Muscular and thyroid pathological changes were independent of selenium supplementation. Selenium supplementation was important for maintaining T3 in ewes and newborn lambs until the 8th week after birth.